Got Schooled! Two Cases of Professors' Return to the Middle School Health and Physical Education Classroom. Issue 1 (2nd January 2023) - Grube, Dan; Little, Stephanie
Abstract: Successful educator preparation programs rely on partnerships with k-12 schools. The literature emphasizes the importance of strong partnerships, but illustrates limitations in creating and maintaining partnerships that meet the needs of all parties – the partnering school and its students, the college/university and teacher candidates. The purpose of this article is to share valuable lessons learned from two professors' return to the field.